3 Tesla MR imaging of the large endolymphatic duct and sac anomaly with audiological correlation. Issue 145 (December 2021) - Parlak, Safak; Akgoz Karaosmanoglu, Ayca; Ozbal Batuk, Merve; Sennaroglu, Levent; Ozgen, Burce
Highlights: High-resolution imaging of LEDS anomaly reveals a spectrum of cochlear anomalies. Modiolar deficiency can be seen as an isolated cochlear anomaly in LEDS. 3 T imaging reveals no cochlear anomaly in some ears despite severe LEDS or profound HL. Abstract: Purpose: Large endolymphatic duct and sac (LEDS) is one of the most common imaging abnormalities in congenital sensorineural hearing loss and is frequently seen with coexistent cochlear anomalies, especially incomplete partition type II. However, MRI findings of accompanying cochlear and especially modiolar dysplasias may be subtle. The purpose of this study is to evaluate the imaging findings of LEDS with high-resolution imaging at 3 T and correlate with the audiological data. Methods: 3 T temporal bone MRIs of 54 ears in 30 LEDS patients were retrospectively evaluated. The cochlear dysmorphism and modiolar deficiency were assessed qualitatively and quantitatively. The severity of LEDS anomaly, the signal changes within the LEDS and cochlea were also noted. The imaging findings were correlated to the audiological data. Results: The cochlea was abnormal in 77.8% of the ears with an isolated modiolar deficiency in 11.1%. Cochlea and modiolus were completely normal in 11.1% of the ears. In 63% of the ears X-distance was increased. T2 hypointensity within LEDS and cochlea were detected in 42.6%, and 7.4% of the ears, respectively. The median diameters of LEDS were higher in ears with severe to profound HL than ears with normal to moderate HL (p < 0.05). The X-distance, presence of T2 hypointensity within LEDS, and diameters of modiolus did not show statistical correlation with the audiographic data. Conclusion: High-resolution 3 T imaging of patients with LEDS anomaly revealed a spectrum of cochlear anomalies, but up to 11.1% of the ears had no underlying anomaly despite severe (endolymphatic duct/sac) dilatation and/or profound HL.